The PENGARUH RETURN ON ASSETS (ROA) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PERUSAHAAN INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021-2025 - Aida Rosyi; Noor Hidayati; Nurul Wahyuni; Rizki Muslim Hidayat (Smart Business Journal (SBJ), 2026)
This study examines the effect of Return on Assets (ROA) and Earnings Per Share (EPS) on stock prices of companies listed on the LQ45 index of the Indonesia Stock Exchange during the 2021–2025 period. This study uses an exploratory quantitative design with secondary data obtained from annual financial reports. The sample was selected using purposive sampling, resulting in 50 observations from 10 LQ45 companies over five years. Data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results show that ROA and EPS have a significant effect on stock prices, both partially and simultaneously. These results indicate that ROA and EPS are important financial indicators that investors can use to make investment decisions and are factors that influence stock prices.